2013
DOI: 10.1038/jcbfm.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Spatial Covariance Analysis of 99MTc-Exametazime SPECT Images in Dementia with Lewy Bodies and Alzheimer'S Disease: Utility in Differential Diagnosis

Abstract: We examined 99m Tc-exametazime brain blood flow single-photon emission computed tomography (SPECT) images using a spatial covariance analysis (SCA) approach to assess its diagnostic value in distinguishing dementia with Lewy bodies (DLB) from Alzheimer's disease (AD). Voxel SCA was simultaneously applied to a set of preprocessed images (AD, n ¼ 40; DLB, n ¼ 26), generating a series of eigenimages representing common intercorrelated voxels in AD and DLB. Linear regression derived a spatial covariance pattern (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…The multivariate SCA approach offers practical advantages over traditional univariate methods in radioligand image analysis, since SCA is concerned only with inter-voxel correlations and does not rely upon any absolute quantification in uptake which requires either information of a distribution volume from arterial blood sampling or selection of a suitable reference tissue/region. It has also been demonstrated that the multivariate SCA technique is superior relative to univariate procedures in differentiating AD from controls [22] and AD from dementia with Lewy bodies [12]. We found a voxel SCP derived from 123 I-QNB SPECT scans that significantly differentiated AD from controls.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The multivariate SCA approach offers practical advantages over traditional univariate methods in radioligand image analysis, since SCA is concerned only with inter-voxel correlations and does not rely upon any absolute quantification in uptake which requires either information of a distribution volume from arterial blood sampling or selection of a suitable reference tissue/region. It has also been demonstrated that the multivariate SCA technique is superior relative to univariate procedures in differentiating AD from controls [22] and AD from dementia with Lewy bodies [12]. We found a voxel SCP derived from 123 I-QNB SPECT scans that significantly differentiated AD from controls.…”
Section: Discussionmentioning
confidence: 77%
“…One form of voxel spatial covariance analysis (SCA) is the scaled subprofile model (SSM), an extension of principal component analysis (PCA), which generates a series of PCA eigenimages of brain uptake, representing significant sources of variance in the data that may indicate specific disease features. These procedures have previously been applied successfully to glucose metabolism PET and perfusion SPECT imaging data in AD [12,22,25,46] and Parkinson's disease (PD) [3,16,33]. Multivariate approaches thus may afford a unique perspective on receptor alterations as a result of neurodegenerative disease given the complex inter-dependency between cortical and subcortical regions in receptor levels, as a result of either direct neuropathological change or consequent up-/down-regulation of receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Occipital hypoperfusion on SPECT [49] or hypometabolism on PET [50] is more typical of DLB than AD, and represents a potential marker of DLB. Occipital hypometabolism and relative preservation of the posterior cingulate gyrus distinguished DLB from AD patients with a sensitivity of 77% and a specificity of 80% [51].…”
Section: Neuroimagingmentioning
confidence: 99%
“…In addition, more recently we have shown that a multivariate approach can usefully discriminate between DLB and AD with high sensitivity and specificity (Colloby et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%